Cytokines, serum neopterin, and CDreactive proD tein levels in myocardial infarction patients - G. E. Kubensky; S. A. Chernov; S. V. Skvortsov; V. N. Shebankova (Российский кардиологический журнал, 2005)
In 46 patients with acute Q-wave myocardial infarction (MI), some parameters of cell immunity (interleukins (II) 1, 6, 10, tumor necrosis factor (TNF) alpha, serum neopterin); C-reactive protein level; virus agents (Herpex simplex, Cytomegalovirus, Chlamydia pneumoniae) - PCR reaction; IgM and IgG levels were assessed. Cell immune dysbalance -pro-inflammatory factor activation (II 6, FNO, serum neopterin) - was observed. Most patients had persistent virus infection - mostly, by Herpes simplex. This immune dysbalance, unrelated to myocardial damage, was more severe in complicated MI clinical course (recurrent angina, congestive heart failure, paroxysmal arrhythmias).